2006
DOI: 10.1104/pp.105.076331
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Primary Target Genes of Phytochrome Signaling. Early Transcriptional Control during Shade Avoidance Responses in Arabidopsis

Abstract: The phytochrome (phy) photoreceptors modulate plant development after perception of light. Upon illumination of etiolated seedlings, phys initiate a transcriptional cascade by directly transducing light signals to the promoters of genes encoding regulators of morphogenesis. In light-grown plants, however, little is known about the transcriptional cascade modulated by phys in response to changes in light. The phy entry points in this cascade are completely unknown. We are particularly interested in the shade av… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
194
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(202 citation statements)
references
References 68 publications
(111 reference statements)
7
194
1
Order By: Relevance
“…We define those genes with FIR values >1.5 as being moderately to robustly dependent on the four PIFs for shade responsiveness (Table 1) and those with FIR values <1.5 as being marginally to minimally dependent on these PIFs for shade responsiveness (see Supplemental Data Set 18 online). Several genes previously well documented as rapidly shadeinduced marker genes, including ARABIDOPSIS THALIANA HOMEOBOX PROTEIN2 (ATHB2), XTR7, HFR1, PHY RAPIDLY REGULATED1 (PAR1), and INDOLE-3-ACETIC ACID INDUC-IBLE29 (IAA29) (Roig-Villanova et al, 2006, 2007Carabelli et al, 2007;Lorrain et al, 2008), are identified here as being robustly dependent on the PIF quartet for this rapid shade responsiveness (Table 1; see Supplemental Data Set 18 online).…”
Section: Identification Of Pif-dependent Rapidly Shade-responsive Genesmentioning
confidence: 77%
“…We define those genes with FIR values >1.5 as being moderately to robustly dependent on the four PIFs for shade responsiveness (Table 1) and those with FIR values <1.5 as being marginally to minimally dependent on these PIFs for shade responsiveness (see Supplemental Data Set 18 online). Several genes previously well documented as rapidly shadeinduced marker genes, including ARABIDOPSIS THALIANA HOMEOBOX PROTEIN2 (ATHB2), XTR7, HFR1, PHY RAPIDLY REGULATED1 (PAR1), and INDOLE-3-ACETIC ACID INDUC-IBLE29 (IAA29) (Roig-Villanova et al, 2006, 2007Carabelli et al, 2007;Lorrain et al, 2008), are identified here as being robustly dependent on the PIF quartet for this rapid shade responsiveness (Table 1; see Supplemental Data Set 18 online).…”
Section: Identification Of Pif-dependent Rapidly Shade-responsive Genesmentioning
confidence: 77%
“…Analysis of phytochrome mutants has demonstrated that, in Arabidopsis, phyB, phyD and phyE are the major phytochromes inhibiting shade avoidance (Devlin et al, 1998;Franklin et al, 2003). The search for genes up-regulated in response to shade led to the identification of several transcription factors that are very rapidly induced in response to low R/FR ratios (Carabelli et al, 1993;Devlin et al, 2003;Roig-Villanova et al, 2006;Salter et al, 2003;Sessa et al, 2005). Functional characterization of these genes indicated that, while ATHB-2 promotes growth responses associated with shade, HFR1 is part of a negative branch preventing 'over-reaction' in response to canopy light (Roig-Villanova et al, 2006;Salter et al, 2003;Sessa et al, 2005;Steindler et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…The search for genes up-regulated in response to shade led to the identification of several transcription factors that are very rapidly induced in response to low R/FR ratios (Carabelli et al, 1993;Devlin et al, 2003;Roig-Villanova et al, 2006;Salter et al, 2003;Sessa et al, 2005). Functional characterization of these genes indicated that, while ATHB-2 promotes growth responses associated with shade, HFR1 is part of a negative branch preventing 'over-reaction' in response to canopy light (Roig-Villanova et al, 2006;Salter et al, 2003;Sessa et al, 2005;Steindler et al, 1999). As ATHB-2 and PIL1 expression is constitutively high in phy mutants, especially in the phyB phyD phyE triple mutants, the high level of their mRNA during shade conditions may result from a phytochrome-dependent de-repression mechanism (Salter et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, PHYB transcripts did accumulate with the addition of green light, consistent with the increases observed by Devlin et al (2003) in response to far-red light. The HY5 transcript has been well described in photomorphogenic responses, yet it is not required for transducing shade-triggered signals (Roig-Villanova et al, 2006). Here, this transcript serves as an additional non-shade-associated message that is sensitive to changing light environments, and its levels also increase.…”
Section: Discussionmentioning
confidence: 99%
“…PIL1 encodes a bHLH transcription factor and is a member of the PIF transcription factor family. It has been described to play an important negative role in long-term shade avoidance syndrome in a phyB background, aside from its effect on shade stimulation (Roig-Villanova et al, 2006). The transcript levels of HAT4 and PIL1 are welldescribed molecular signatures of the shade response.…”
Section: Discussionmentioning
confidence: 99%